Diffusion approximation of the Wright-Fisher model of population genetics: Single-locus two alleles - Coad, R.W. (Український математичний журнал, 2000)
We investigate an autoregressive diffusion approximation method applied to the Wright-Fisher model in population genetics by considering a Markov chain with Bernoulli distributed independent variables. The use of an autoregressive diffusion method and an averaged allelic frequency process lead to an Orn-stein-Uhlenbeck diffusion process with discrete time. The normalized averaged frequency process possesses independent allele frequency indicators with constant conditional variance at equilibrium. In a monoecious diploid population of size N with r generations, we consider the time to equilibrium of averaged allele frequency in a single-locus two allele pure sampling model. Досліджується авторегресивна дифузійна апроксимація моделі Райта — Фішера популяційної генетики. Для цього використовується марковський ланцюг з незалежними змінними, підпорядкованими розподілу Бернуллі. Методи авторегресивної дифузії та усереднення алельних частот дозволяють звести проблему, що вивчається, до дифузійного процесу Орнстейна -Уленбека з дискретам часом, Нормований процес усереднених частот має в стані рівноваги незалежні індикатори алельних частот з постійною умовною дисперсією. Встановлюється час, потрібний однодомній деплоїдній популяції розміром N, що складається з r поколінь, для того щоб досягти стану рівноваги усереднених алелрьних частот в однолокусній двоалельній моделі.